Systemic risk and competition revisited - Silva-Buston, Consuelo (Journal of Banking & Finance, 2019)
This paper revisits the mechanism behind the relation between bank competition and systemic risk. I decompose this risk into a component driven by banks’ commonality with the market and a component arising from other sources of interbank commonality. I show that competition is negatively related to the latter. This relationship is stronger for more informationally opaque banks, financed with a larger share of uninsured sources and in countries with lower deposit insurance coverage. The findings are consistent with herding incentives at banks when competition is low.